Reading queer counter-narratives in the high-school literature classroom: possibilities and challenges. Issue 6 (1st November 2016) - Helmer, Kirsten
ABSTRACT: Drawing on an ethnographic case study of a 13-week Gay and Lesbian Literature course, this paper explores how a high-school teacher and her students engaged with queer-themed literature. Focused on episodes around the class' engagement with two of the novels read in the course – Rita Mae Brown's Rubyfruit Jungle and Michael Cunningham's The Hours – the paper offers insights into how these queer counter-narratives opened up spaces for unanticipated queer moments which intervened disruptively into the heteronormative space of the English literature classroom, while also revealing the persistency of heteronormative discourses. This research raises questions about the pedagogical frameworks which guide the implementation of curricula focused on lesbian, gay, bisexual, transgender, and queer topics in secondary schools. I suggest that queer counter-narratives provide productive sites where teachers and their student readers can negotiate the paradoxes of contemporary queer subjectivities as they wrestle with notions of identity, normalcy, and norms related to diverse sexualities and genders.